Resource of Received Knowlodge upon the Contemporary Imamiyyah Shia and Its Correlation with the Classical Scholars| مصدر التلقي المعرفي لدى الشيعة الإمامية المعاصرين وعلاقته بالقدامي - Kholid Muslih (Al-Zahra : Journal for Islamic and Arabic Studies, 2014)
Unlike the other sects, especially the Ahlussunah, Twelver Shia or the Imamiyyah havestructure as well as a unique source of knowledge; where they believe that those oftwelve Imams are as an authentic source of knowledge other than Allah and Hismessenger. Whole words, actions and decisions of the Prophet and those Imams werecodified by the authors in a book known as "al-Uşūl al-Mudawwanāt wa al-hadīthah alşughrā"or "al-Kutub al-arbaʻah". Just like "al-Kutub al-Sittah" or "al-Kutub at-Tisʻah" inthe scientific tradition of the Ahlussunah. These books of hadith are as the majorreferences after the Quran in the scientific structure of the classical Shia scholars. As asource of knowledge, the position of these four books of hadith -especially al-Kāfī- hasnot been replaced until now. The scholars' contemporary Shia still regard it as the mostauthentic source after the Quran. It can be concluded that the structure and sources ofknowledge of the scholars' contemporary Shia is not different with the structure andsources of the classical knowledge.